Learning Recovery Plan (LRP) in Addressing Learning Gaps of Effective and Efficient Learning Outcomes after Pandemic among Different School in the Division of San Pablo - Dionglay, Perlyn V.; Callo, Eden C. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
The Department of Education (DepEd) adopts the National Learning Recovery Program (NLRP) through DepEd Order No. 013, s. 2023 which aims to strengthen the learning recovery and continuity program, improve literacy and numeracy, and accelerate the achievement of education targets. This study aimed to examine the respondents perceptions on the implementation of the Learning Recovery Plan (LRP) in addressing the learning gaps, starts with assessing fundamental skills such as the literacy and numeracy in the early grades. Detecting learners who have not developed the full range of reading and numeracy skills are provided with appropriate programs. A post pandemic program from the Department of Education, that which aims to identify the level of responsiveness, relevance and appropriateness of the different school in the Division of San Pablo City, and how effective and efficient is this study as to upskilling and reskilling of teachers, stakeholders effort, updating, review of different projects and programs and teaching methodology to recover the learning gaps after pandemic. Random sampling was conducted because of the limited access for face to face contact and all the big schools, three-year plan beginning SY 2022-2023, which shall be adopted by all DepEd implementing units and schools by aligning respective plans and implementation to the directions and priorities specified in this policy. Based on the finding the relevance, resilience and appropriateness in the level of in the implementation of learning recovery plan (LRP)addressing the learning gaps are “always observed” among the different school in the division of San Pablo regardless of age, length of service and district from which they belong, moreover the level of effectivity and efficiency in the learning, have significant effect in terms of physical and mental resilience, communication plan, professionalism , community stakeholder and support system in upskilling and reskilling of teachers, stakeholders effort, improvement of learning environment, updating and review of projects and programs and the teaching methodology.